A flexible fibrous membrane based on copper(ii) metal–organic framework/poly(lactic acid) composites with superior antibacterial performance. (23rd April 2021) - Liu, Zhao; Ye, Junwei; Rauf, Abdul; Zhang, Siqi; Wang, Guangyao; Shi, Suqi; Ning, Guiling
Abstract : A flexible fibrous membrane was prepared by electrospinning a Cu(ii )-based MOF and poly(lactic acid), which showed excellent broad-spectrum antibacterial properties based on the steady and prolonged release of Cu 2+ in biocidal concentrations. Abstract : A flexible antibacterial fibrous membrane employing high antibacterial efficiency has great potential in healthcare applications. Herein, a three-dimensional copper(ii ) metal–organic framework [Cu2 (CA)(H2 O)2, Cu-MOF-1] and poly(lactic acid) (PLA) composite fibrous membrane was prepared through a facile electrospinning method. The sphere-like Cu-MOF-1 was rapidly synthesized by a microwave-assisted hydrothermal reaction of Cu(ii ) salts with citric acid (H4 CA) in the presence of polyvinyl pyrrolidone (PVP). The surface morphology, thermal stability, mechanical properties and hydrophilicity test of the as-prepared Cu-MOF-1/PLA fibrous membrane were studied systematically. Compared with commercial copper nanoparticles (Cu-NPs), citric acid and copper citrate, Cu-MOF-1 showed higher antibacterial properties with the bacteriostatic rates of 97.9% and 99.3% against Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ), respectively, when the used dose was 250 μg mL −1 . The Cu-MOF-1/PLA fibrous membrane also exhibited outstanding bactericidal activities against E. coli and S. aureus with the antibacterial rates up to 99.3% and 99.8%, respectively. Mechanism investigation indicated that the slowly released Cu 2+ ions could destroy the microenvironment of bacteria cells and destroy the integrity and permeability of the cell membrane, leading to enzyme inactivation. Therefore, the as-prepared flexible fibrous membrane will advance progress toward developing a broad spectrum antibacterial textile for healthcare protection related applications.